Is Tibet China’s Colony: The Claim of Demographic Catastrophe - Sautman, Barry (Columbia Journal of Asian Law, 2001)
Although the world’s states universally recognize that Tibet is part of China, the discourse on Tibet in the West and parts of Asia has largely been one of Tibet as a colony. Tibetan émigrés in India and grassroots foreign supporters have expectedly played a key role in positioning the discourse as anti-colonial. Based on the authority of the Dalai Lama, antagonism towards the Chinese Communist Party (CCP) regime and other factors, they have succeeded in eliciting support for the Tibet-as-colony position from politicians, journalists and a few scholars. The Tibet-as-colony position is not the metaphorical use of colonialism that many scholars deplore as a turning away from the specific historical realities of colonialism. Rather, proponents of the concept aim to establish that Tibet is as much a colony as were the lands held by European powers, the US and Japan from the 16th to late 20th centuries. Tibet, they argue, thereby takes on a right to self-determination, including independence. Indeed, proposals for association, federation and “genuine autonomy” for Tibet, successively advanced by the émigrés since 1987, have incorporated the right to self-determine Tibet’s territorial status or mode of governance. If, per contra, Tibet is not a colony, self-determination is not required and a compromise must then be forged. It would likely involve retaining Tibet’s status as part of China and much of its governance system, but with power shared by the CCP and the Dalai Lama’s forces, a solution that is now within the contemplation of some Tibet specialists in the People’s Republic of China (PRC).